Organized Crime as a Current Political-Security Challenge - Dimitriev, Emil (Филозофски факултет, 2023)
Abstract: Undoubtedly today one of the most current topics in the world is organized crime. A topic regularly represented in the dialogues at the political, economic and security level. The world is increasingly occupied by threats from this criminal form, which seems to be gaining in intensity with the process of globalization and technological development Crime itself and its organization are complex to analyse, let alone to combine and form a whole, and that whole to be scientifically defined. It is to be expected that discussions and definitions will be controversial i.e., no unified definition would be possible. Organized crime in modern society is a threat to the legal order and undermines democratic institutions in every society. Its influence cannot be limited to criminal groups and crime, but must be seen in the context of the state and society as a whole. Some scholars define it as a supranational and overstate organization with exceptional power, increasingly perceived as a security issue. Despite numerous different views on the definition, there is scientific consensus that it is a relatively recent form of crime. From today’s perspective, there is hardly a country without organized crime as a focus of interest. Globalization and the more numerous international institutions also have this phenomenon high on their agendas. There is a common interest in creating effective methods and mechanisms to act preventively and counter all forms of organised crime. Organized crime is approached as a security issue rather than isolated criminal acts, reaching into the area of terrorism as the highest form of security threat. In many cases terrorism uses the groups, the methods, and the means of organized crime. Having in mind its internationality and the question of global security, this type of crime like no other form of crime is transnational.
Keywords: organised crime, society, security, prevention, influence.